2020
DOI: 10.29103/jtku.v9i1.3072
|View full text |Cite
|
Sign up to set email alerts
|

Produksi Minyak Alpukat dari Daging Buah Alpukat Gayo Dengan Metode Ekstraksi Menggunakan Pelarut N-Heksan Untuk Aplikasi dalam Sabun Mandi Herbal

Abstract: Ekstraksi adalah suatu proses pemisahan suatu zat berdasarkan perbedaan kelarutannya terhadap dua cairan tidak saling larut yang berbeda. Adapun metode yang digunakan pada penelitian ini adalah metode ekstraksi soklet dengan pelarut n-heksana. Dengan metode ekstraksi kehilangan minyak dalam proses lebih sedikit, sehingga minyak yang dihasilkan lebih banyak. Penelitian ini bertujuan yaitu untuk mengetahui pengaruh waktu dan suhu ekstraksi pada proses pengambilan minyak alpukat yang menghasilkan karakteristik mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
1
1
1
Order By: Relevance
“…This study resulted in yield of avocado oil ranging from 43.88 to 47.95% (Table 3). The yields obtained are greater than those reported by Ginting et al [9] i.e., between 24.64-46.72% for the production of avocado oil for herbal bath soap applications. Arpi et al [10] reported that the pre-treatment of with water boiling showed yield of 32.36-38.13%, which was lower than the yield obtained in this study.…”
Section: Optimization Of Process Parameter Conditionscontrasting
confidence: 66%
See 1 more Smart Citation
“…This study resulted in yield of avocado oil ranging from 43.88 to 47.95% (Table 3). The yields obtained are greater than those reported by Ginting et al [9] i.e., between 24.64-46.72% for the production of avocado oil for herbal bath soap applications. Arpi et al [10] reported that the pre-treatment of with water boiling showed yield of 32.36-38.13%, which was lower than the yield obtained in this study.…”
Section: Optimization Of Process Parameter Conditionscontrasting
confidence: 66%
“…Figure 2 shows how CaCO3 concentration and extraction temperature affect the percent response value (%) yield of avocado oil produced. Ginting et al [9] revealed that a long extraction time makes the contact between the solvent and the material to be extracted is longer, the diffusion rate of the solvent into the solid is greater and the circulation becomes longer and this is what causes the resulting yield to be greater. Temperature can also affect yield results because an increase in temperature can cause the pores of the solid to expand so that the solvent easily diffuses into the pores of the solid so that it can dissolve avocado oil.…”
Section: Optimization Of Process Parameter Conditionsmentioning
confidence: 99%
“…Lemak pada alpukat didominasi asam lemak tak jenuh tunggal atau asam oleat yang bersifat sebagai anti oksidan dan mengkonsumsinya dapat menekan kadar kolesteral dan hipertensi (Sariningsih & Srimiati, 2018;Khusuma et al, 2020). Lemak alpukat juga berpotensi sebagai bahan utama dalam pembuatan sabun mandi herbal bebas alkali dengan karakteristik yang sesuai dengan Standar Mutu Sabun (SNI 06-3532-1994) (Ginting et al, 2020). Karena hal tersebut di atas, pemilihan varietas dengan kadar lemak tinggi menjadi penting untuk efisiensi pemanfaatan lemaknya.…”
Section: A B C Dunclassified